Motor cortical excitability during voluntary inhibition of involuntary tic movements. Issue 11 (31st October 2018) - Ganos, Christos; Rocchi, Lorenzo; Latorre, Anna; Hockey, Leanne; Palmer, Clare; Joyce, Eileen M.; Bhatia, Kailash P.; Haggard, Patrick; Rothwell, John
ABSTRACT: Background : Tics can be voluntarily inhibited. However, the neurophysiology of voluntary tic inhibition remains underexplored. The objective of this study was to explore state‐dependent effects of voluntary tic inhibition on M1 excitability. Methods : Neurophysiological assessments (single motor‐evoked potentials, corticospinal recruitment curves, short‐interval intracortical inhibition, H‐reflex) were performed in 14 adults with Tourette syndrome during voluntary tic inhibition and free ticcing. Regressions between behavioral performance and neurophysiological measures were also performed. Results : Voluntary tic inhibition reduced corticospinal excitability: the greater the ability to inhibit tics, the greater was the reduction in excitability. Voluntary tic inhibition was not associated with changes in the excitability of short‐interval intracortical inhibition or the H‐reflex. Conclusions : Voluntary inhibition of tics reduces the excitability of corticospinal output. The pattern of neurophysiological findings is consistent with a withdrawal of excitation, but not with modulation of the inhibitory interneuronal mechanisms involved in short‐interval intracortical inhibition. © 2018 International Parkinson and Movement Disorder Society